Temperature-Sensitive Mutations of the Photosynthetic Apparatus of Rhodospirillum rubum - Weaver, Paul (1971)
Temperature-sensitive mutants of Rhodospirillum rubum have been isolated by enrichment techniques selecting for conditionally aberrant electron flow in various portions of the electron transport scheme. The temperature sensitivity of a class of these strains is shown to preferentially affect the photosynthetic mode of growth and energy production over the aerobic mode.